Pro inflammatory responses of thp-1 macrophage cell line infected with recombinant bcg (rBCG) expressing the MSP-1C of Plasmodium falciparum - Yen, Pong Sze (Universiti Sains Malaysia, 2013)
Phagocytosis of macrophage is an important innate defence mechanism against malaria parasites. In the presence of parasites, the macrophage gains its proinflammatory responses through the production of pro-inflammatory cytokines and nitric oxide (NO) which allow it to eliminate the parasites from infected red blood cells. In this study, the ability of human macrophage cell line, THP-1 infected with a recombinant BCG (rBCG) clone expressing the 19-kDa C-terminus of the merozoite surface protein-1 (MSP-1C) of Plasmodium falciparum in stimulating proinflammatory responses indicating by phagocytosis activity, the production of IL-12, NO and inducible nitric oxide synthase (iNOS) were determined. The results demonstrated that the phagoctic activity and expression of NO were higher in cells infected with rBCG compared to cells infected with BCG, while no significant differece was observed on the levels of IL-12 production and iNOS protein expression by these cells. Thus, this study shown that the rBCG vaccine might had the potential to be used as innate immune activator for malaria infection. However, further investigations must be carried out to prove the hypothesis. xiii Phagocytosis of macrophage is an